Track analysis of the Neotropical Entimini (Coleoptera: Curculionidae: Entiminae) - Romo,Alberto (2011)
Track analysis of the Neotropical Entimini (Coleoptera, Curculionidae, Entiminae). Distributional patterns of the species belonging to the tribe Entimini from the Neotropical region were analyzed. Based on a track analysis of 22 species of Entimus, Rhigus, and Phaedropus, for which distributional data were available, two generalized tracks were found. One is located in northern Brazil, corresponding to the Amazonian subregion, and is determined by Phaedropus candidus and Rhigus speciosus. The other is located in southern Brazil, corresponding to the Parana subregion, and is determined by Entimus imperialis, E. excelsus, Phaedropus togatus, Rhigus dejeanii, R. faldermanni, R. horridus, R. lateritus, R. nigrosparsus, and R. tribuloides. The development of the Chacoan subregion is hypothesized to have been the dynamic vicariant event that fragmented the former Amazonian-Parana forest.